Impact of the COVID-19 pandemic on the quality of life of early breast cancer patients undergoing adjuvant chemotherapy – an observational, multicenter study - Tuomarila, Marie; Poikonen-Saksela, Paula; Kondylakis, Haridimos; Mattson, Johanna; Auvinen, Päivi; Jukkola, Arja; Kalashnikov, Ilja; Koivunen, Jussi; Kääriäinen, Okko-Sakari; Sunela, Kaisa; Utriainen, Meri; Vihinen, Pia; et al. (Medical Journals Sweden AB, 2026)
Background and purpose
We evaluated the impact of the coronavirus disease 2019 (COVID-19) pan-demic on health-related quality of life (HRQoL) in early-stage breast cancer patients receiving adjuvant chemotherapy.
Patients and methods
The study involved 180 patients with stage I–III breast cancer who initiated adju-vant chemotherapy between June 2020 and May 2021. The pre-pandemic comparison data included 113 early breast cancer patients who began adjuvant chemotherapy between November 2018 and August 2019. HRQoL was assessed using the EORTC QLQ-C30 at baseline and again after 3 and 6 months. The sub-scales were compared between the COVID-19 pandemic and the pre-pandemic eras.
Results
We observed deterioration on almost all HRQoL subscales of the patients treated during the pan-demic from baseline to 3 months. After the chemotherapy at 6 months, the scales remained deteriorated, whereas only appetite loss and emotional functioning improved. A comparison between the pandemic and the pre-pandemic eras revealed that several HRQoL subscales showed better results during chemo-therapy in the pandemic era. Global health and role functioning at 6 months presented declined levels during the pandemic.
Interpretation
The well-being of breast cancer patients during the chemotherapy treatment in the pandemic era was moderately better than in the pre-pandemic era. Patients in the pandemic era might have reported fewer symptoms during the treatment, as the focus was on the COVID-19 pandemic and its restrictions.